The compositional analysis of hunter-gatherer pottery from the Kuril Islands - Gjesfjeld, E (Elsevier, 2018)
© 2016 Elsevier Ltd Archaeological analysis of pottery remains from Northeast Asia has traditionally emphasized macroscopic traits such as decoration and vessel form. While these features are important in characterizing the cultural affiliation of pottery, compositional analysis can provide new lines of evidence that highlight social processes such as migration and exchange. Using a ceramic assemblage recovered from the Kuril Islands of Northeast Asia, this research investigates the regional exchange of pottery associated with the Epi-Jomon and Okhotsk cultural traditions. Results of this study indicate cultural differences highly influence the geographic distribution of compositional groups and patterns of regional exchange. This research was funded by a Doctoral DissertationImprovement Grant from the National Science Foundation Division ofPolar Programs-Arctic Social Sciences (Award #1202879).